Studi Komparasi Penerapan Model Pembelajaran Problem Based Learning dan Inkuiri Terbimbing terhadap Keterampilan Proses Sains Siswa Kelas X SMA Negeri 3 Boyolali Tahun Pelajaran 2013/2014 - Muhamad Yutam Soleh; Slamet Santosa; Meti Indrowati (BIO-PEDAGOGI, 2014)
The purpose of this research are to determine the differences result in Sciences Process Skills (SPS) with using Problem Based Learning and guided inquiry of X grade students at SMA Negeri 3 Boyolali  in 2013/2014 academic year. This research was quasi experiment research which used Posttest Only With Nonequivalent Control Group design by using the experimental 1 class (application of Problem Based Learning) and experimental 2 class (application of guided inquiry). The population studies are all X class students of SMA Negeri 3 Boyolali in academic year 2013/2014. Sampling technique is using cluster sampling, the classroom that is chosen are X.1 as the experiment 1 class and X.3 as the experimental 2 class. The techique of collecting data is using essay test for measuring of SPS classifying, using tool and material, hypothesizing, formulate ways of working, predicting and communicating. Non-test technique is using methods of documentation and observation methods for measuring of SPS using the tool and material, observing and experimenting. The data were analyzed by t-test assisted SPSS 16. The result of this research concluded that there are differences results between Problem Based Learning and guided inquiry toward student’s sciences process skills of X grade students at SMA Negeri 3 Boyolali. Key Words: Problem Based Learning, Guided Inquiry, Science Process Skills